470 Redo Mitral Valve Surgery via Median Sternotomy Versus Mini-Thoracotomy: A Systematic Review and Meta-Analysis of Clinical Outcomes. (19th August 2022) - Shirke, M; Ravikumar, N; Tan, S; Mutsonziwa, N; Soh, V; Harky, A
Abstract: Aim: Redo mitral valve surgery is a high-risk cardiac procedure. Median re-sternotomy (MS) remains a common approach in many centres. However, there is a significant risk of morbidity and mortality associated with this approach. Alternative procedures such as the right anterolateral minithoracotomy (MT) have been explored. This review compares the clinical outcomes of re-sternotomy versus right mini thoracotomy in mitral valve surgery. Method: A systematic, electronic search was performed according to PRISMA guidelines to identify relevant articles that compared outcomes of the MS versus MT procedures in redo mitral valve surgery. Data regarding mortality, length of hospital stay, stroke, infection were extracted and analysed Results: Thirteen studies were identified, enrolling 4, 549 patients. Length of hospital stay (MD= -3.70, 95% CI[-4.89, -2.51]), 30-day mortality (OR=0.58, 95% CI[0.39, 0.87]), new-onset renal failure (OR=0.38, 95% CI [0.22, 0.65], and length of ICU stay (MD=-0.62, 95% CI[-1.21, 0.02]) were statistically significant in favour of the MT approach. Infection rates (OR=0.52, 95% CI[0.24, 1.12]) were lower in the MT group; however, the difference was not significant. No significant differences were observed in the CPB time (MD=-2.68, 95% CI[-8.53, 3.17]), aortic cross-clamp time (MD=-2.40, 95% CI[-17.07, 12.27]), and rates of stroke (OR=1.03, 95% CI[0.55, 1.92]). Conclusions: Right mini thoracotomy is a safe alternative to the traditional re-sternotomy for patients who have had previous cardiac surgery. The approach offers a reduced length of hospital stay, ICU stay, and a lower risk of new onset renal failure requiring dialysis. This review calls for robust trials in the field to further strengthen the evidence.